Efeitos de etanol e bebida energética no padrão de sono e na atividade motora de camundongos - Fujisaka, Gabriela Naomi Kowara [UNIFESP] (2009)
Ethanol is a psychotropic substance that presents a "biphasic and dose-dependent effect". In low doses, it induces euphoria and agitation, while in high doses it induces predominantly depressant effects, mainly on motor activity and sedation. A dramatic rise in consumption of energy drinks, combined or not with ethanol, has been observed, and people have reported drinking the mixture to increase the stimulant effect of ethanol and decrease the depressant one. In studies conducted with mice, it was observed that acutely, the mixture of ethanol with energy drinks increases the locomotor activity. After chronic administration, the mixture also increases sensitization to the stimulant effect of ethanol. Due to the paucity of studies on the effects of co-administration of energy drinks and high dose of ethanol on locomotor activity and sleep architecture, these were the objectives of the present work. In study 1, it was observed that acutely, energy drink (10.7 ml/kg de RedBull®) presented a stimulant effect on locomotor activity of mice, while ethanol (2.5 g/kg i.p.) presented a depressant effect. Animals treated with these combined drugs presented the same level of locomotor activity of that in the control group, indicating that energy drinks antagonize the depressant effect of ethanol. After chronic treatment with ethanol, animals developed tolerance to the depressant effect of ethanol and only the group treated with the mixture of energy drink and ethanol developed behavioral sensitization to the stimulant effect of ethanol. In study 2, it was confirmed that ethanol causes loss of righting reflex in mice and this effect is dose–dependent. After chronic treatment with ethanol, however, neither development of tolerance nor sensitization to the effects of ethanol has been observed. Acutely and chronically, energy drinks did not alter the effect induced by ethanol on the loss of righting reflex. In study 3, acute oral administration of 4.5 g/kg of ethanol increased time awake and decreased sleep efficiency, NREM sleep and REM sleep. The combined administration of ethanol and energy drinks extended the wakefulness effects induced by ethanol. However, no interaction between ethanol and energy drink has been observed on REM sleep.